Transplacental Antioxidants Inhibit Lung Tumors in Mice Exposed to Cigarette Smoke After Birth: A Novel Preventative Strategy? - Balansky, R.; Ganchev, G.; Iltcheva, M.; E. Steele, V.; De Flora, S. (Current Cancer Drug Targets, 2012)
Birth is characterized by an intense oxidative stress resulting in nucleotide alterations and gene overexpression in mouse lung. We showed that cigarette smoke (CS) is carcinogenic when exposure starts soon after birth and applied this bioassay to evaluate the efficacy of chemopreventive agents. The present study evaluated whether administration of the antioxidants N-acetyl-L-cysteine (NAC) and vitamin C or ascorbic acid (AsA) during pregnancy can protect strain H Swiss mice exposed to CS after birth. Exposure to CS, for 4 months, of newborns from untreated mice resulted in significant alterations at 8 months of life, including alveolar epithelial hyperplasia, emphysema, blood vessel proliferation, microadenomas, adenomas, and malignant tumors in lung, liver parenchymal degeneration and urinary bladder epithelium hyperplasia. Treatment throughout pregnancy with either NAC, a scavenger of reactive oxygen species, or AsA, an electron donor, did not affect fertility, parity, and body weight of newborns. Prenatal antioxidants significantly inhibited most lesions in adult mice exposed to CS since birth. For instance, the incidence of emphysema was reduced from 27.5% in CS-exposed mice that were untreated during pregnancy to 7.1% and 14.0% in those treated prenatally with NAC and AsA, respectively. Lung adenomas were reduced from 34.8% to 16.7% and 9.3%, respectively. Malignant lung tumors were reduced from 13.0% to 4.7% by prenatal AsA. Liver parenchymal degeneration was reduced from 58.0% to 14.3% by prenatal NAC. These data mechanistically support a “transplacental chemoprevention” strategy, aimed at protecting the newborn from oxidative stress and the adult from CS-related diseases appearing later in life.
Keywords: N-acetyl-L-cysteine